The Birth of modern theatre Chekhov's Uncle Vanya in perspective - Mantell, Harold; Olivier, Laurence; Films for the Humanities (Firm). (Princeton, N.J. Films for the Humanities, 1975)
Analyzes Chekhov's dramatic techniques as developed in Uncle Vanya. Includes a performance of the third act of the English translation by Constance Garnett.
English translation by Constance Garnett.
VHS.
Narrator, John Dexter; Editor, Carlo Arcamone.
Lawrence Olivier as Dr. Astrou, Michael Redgrave as Uncle Vanya ; Joan Plowright as Sonya, Rosemary Harris as Yelena.
Keywords: Chekhov, Anton Paulovich -- 1860-1904.; Humanities; Theater art